The Influence of Brand Image and Trust on the Decision to Use Services at PT Angkasa Tour & Travel - Hermawanto, Yusuf; Hayati, Nur (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to explain the variable brand image and consumer trust that affects purchase decisions (decisions to use the service) at PT. Angkasa Tour and Travel, Jakartal. This type of research in this study includes causal research, which is research finding and describing the relationship (cause and effect). The population of Instagram followers of PT Angkasa Tour and Travel (@angkasatour.id). This study used a type of quantitative research using the method of causality. The data collection method used was using a questionnaire. This sampling in this study was conducted using purposive sampling technique so that the sample of 110 respondents was obtained. The method of data analysis used the multiple linear regression using SPSS version 26. The results of the research were conducted using multiple linear regression tests. The results show that partially the two independent variables of this study (brand image=X1) and consumer trust=X2), each variable (brand image=X1) is a significant positive effect on the decision to use the service (Y) and the variable (consumer trust= The findings of this research can serve as a foundation for understanding the brand image and customer trust associated with PT Angkasa Tour & Travel. This understanding may inform the company's strategies aimed at enhancing sales by improving decision-making regarding the use of its services.